Is the effect of economic integration on trade margins time sensitive? Sectoral evidence from Latin America - Florensa, Luis Marcelo (2013)
Fil: Florensa, Luis Marcelo. Universidad Nacional de Córdoba. Facultad de Ciencias Económicas. Instituto de Economía y Finanzas; Argentina.